Pressure vessel design manual - Moss, Dennis R (Butterworth-Heinemann, 2013)
Pressure vessels are closed containers designed to hold gases or liquids at a pressure substantially different from the ambient pressure. They have a variety of applications in industry, including in oil refineries, nuclear reactors, vehicle airbrake reservoirs, and more. The pressure differential with such vessels is dangerous and due to the risk of accident and fatality around their use, the design, manufacture, operation and inspection of pressure vessels is regulated by engineering authorities, guided by legal codes and standards. Pressure Vessel Design Manual is a soluti.